Ostracoda (Arthropoda, Crustacea) subrecente da plataforma continental setentrional do Rio Grande do Norte, Brasil - Silva, Alef Kennedy Rocha da (2019)
The class Ostracoda shows one of the most diverse and abundant fossil records among all animals, as well as a wide stratigraphic distribution (from the Ordovician to the Recent) and cosmopolitan geographical distribution. For these characteristics the ostracods are widely used as ecological and paleoecological proxies. The present dissertation aimed at performing a taxonomic survey of the subrecent Ostracoda fauna of the northern continental shelf of Rio Grande do Norte, Northeast Brazil, as well as to investigate ecological aspects of this fauna. Twenty-one samples were collected with a Van Veen on the inner and outer continental shelf off the Açu River. A total of 63 species, 32 genera and 16 families were identified. Hemicytheridae was the family with the highest genera richness and also with the highest abundance (number of valves / 100g of dry sample). Pellucistoma Coryell & Fields, 1937 and Bythocythere Sars, 1866 were the most abundant genera. Neonesidea Maddocks, 1969, Semicytherura Wagner, 1957 and Paracytheridea Mueller, 1894 presented the highest species richness. Based on the Ostracoda assemblages, the inner and outer regions of the continental shelf were significantly different. Of the 32 genera present in the samples, nine (28.2%) were found only in the external region, four (12.5%) in the internal region and 19 (59.3%) were common in both regions. Among the environmental variables analyzed, depth and sediment type best explained the current distribution of benthic marine ostracodes along the internal and external portions of the continental shelf. The data generated in the present study allow a better understanding of the Ostracoda fauna present in the region, and this information will serve as a basis for new scientific research, as well as the sustainable exploitation of the habitats in which these organisms are found. Increasing knowledge and protection of Ostracoda fauna present on the northern continental shelf of Rio Grande do Norte.